2005
DOI: 10.1007/s00427-004-0463-8
|View full text |Cite
|
Sign up to set email alerts
|

Allelic expression of IGF2 in live-bearing, matrotrophic fishes

Abstract: The parental conflict, or kinship, theory of genomic imprinting predicts that parent-specific gene expression may evolve in species in which parental investment in developing offspring is unequal. This theory explains many aspects of parent-of-origin transcriptional silencing of embryonic growth regulatory genes in mammals, but it has not been tested in any other live-bearing, placental animals. A major embryonic growth promoting gene with conserved function in all vertebrates is insulin-like growth factor 2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 17 publications
2
34
0
Order By: Relevance
“…Our knowledge of imprinting in viviparous animals other than mammals is limited. However, Lawton et al (2005) recently found that the gene Igf2, which is imprinted in mammals, is biallelically expressed in two matrotrophic poeciliids (Poeciliopsis prolifica and Heterandria formosa). Thus, no evidence of an important role of imprinting in poeciliids has been found.…”
Section: Discussionmentioning
confidence: 99%
“…Our knowledge of imprinting in viviparous animals other than mammals is limited. However, Lawton et al (2005) recently found that the gene Igf2, which is imprinted in mammals, is biallelically expressed in two matrotrophic poeciliids (Poeciliopsis prolifica and Heterandria formosa). Thus, no evidence of an important role of imprinting in poeciliids has been found.…”
Section: Discussionmentioning
confidence: 99%
“…Located downstream of IGF2 is the untranslated RNA H19 , which is expressed solely from the maternally derived chromosome [24],[25]. Biallelic expression of IGF2 was discovered in the egg-laying monotreme mammals [26], birds [22],[27] and fish [28], implying that imprinting of this region evolved at the same time as viviparity, 180-210MYA [29].…”
Section: Introductionmentioning
confidence: 99%
“…The phylogenetic distribution of known cases of vertebrate imprinting suggests that imprinting evolved in the mammalian line at about the same time as the placenta, when therians diverged from monotremes. The absence of Igf2 imprinting in two poeciliid fish (Lawton et al 2005) that have independently evolved placentas (Reznick et al 2002), however, means that the origin of the mammalian placenta was not a sufficient condition for the origin of imprinting.…”
Section: Introductionmentioning
confidence: 99%